Extensive intracranial haemorrhage as a complication of acute lymphoblastic leukaemia with hyperleukocytosis. (June 2019) - Lim, Wei Kang; Fong, Choong Yi; Li, Limin; Foo, Jen Chun; Yap, Tsiao Yi
Highlights: Expand neuroradiological features of intracranial haemorrhage with hyperleukocytosis. First to show MRI features of predominant widespread juxtcortical and deep grey matter. Importance of prompt chemotherapy in intracranial haemorrhage with hyperleukocytosis. Abstract: We report a rare case of distinctive extensive punctate intracranial haemorrhage associated with acute lymphoblastic leukaemia with hyperleukocytosis. A 7-year-old girl presented with hyperleukocytosis (white cell count 788.7 × 10 9 /L; 94% peripheral blasts) and laboratory tumour lysis syndrome. The diagnosis of T-cell acute lymphoblastic leukaemia was established and confirmed by immunophenotyping of peripheral blood and chemotherapy was commenced promptly. On day 3 of treatment, she developed progressive encephalopathy, left sided hemiparesis with left 6th and upper motor neuron 7th cranial nerve palsy. Brain MRI scan showed extensive punctate haemorrhages with perilesional oedema over the frontal, parietal, occipital, temporal, brainstem and cerebellar regions. The lesions were predominantly over the juxtacortical grey matter. She made a full neurological recovery after 3 months. Our report widens the neuroradiological features of intracranial haemorrhage associated with hyperleukocytosis and highlights the importance of prompt chemotherapy in these patients.